Identity poetics : race, class, and the lesbian-feminist roots of queer theory - Garber, Linda (Between men--between women., 2001)
"Queer theory," asserts Garber, "alternately buries and vilifies lesbian feminism, missing its valuable insights and ignoring its rich contributions." Rejecting the either/or choice between lesbianism and queer theory, this book favors an inclusive approach that defies current factionalism. In an eloquent challenge to the privileging of queer theory in the academy, Garber calls for recognition of the historical--and intellectually significant--role of lesbian poets as theorists of lesbian identity and activism